Association of Central Adiposity With Adverse Cardiac Mechanics: Findings From the Hypertension Genetic Epidemiology Network Study. (June 2016) - Selvaraj, Senthil; Martinez, Eva E.; Aguilar, Frank G.; Kim, Kwang-Youn A.; Peng, Jie; Sha, Jin; Irvin, Marguerite R.; Lewis, Cora E.; Hunt, Steven C.; Arnett, Donna K.; Shah, Sanjiv J.
Abstract : Background—: Central obesity, defined by increased waist circumference or waist:hip ratio (WHR), is associated with increased cardiovascular events, including heart failure. However, the pathophysiological link between central obesity and adverse cardiovascular outcomes remains poorly understood. We hypothesized that central obesity and larger WHR are independently associated with worse cardiac mechanics (reduced left ventricular strain and systolic [s′] and early diastolic [e′] tissue velocities). Methods and Results—: We performed speckle-tracking analysis of echocardiograms from participants in the Hypertension Genetic Epidemiology Network (HyperGEN) study, a population- and family-based epidemiological study (n=2181). Multiple indices of systolic and diastolic cardiac mechanics were measured. We evaluated the association between central obesity and cardiac mechanics using multivariable-adjusted linear mixed-effects models to account for relatedness among participants. The mean age of the cohort was 51±14 years, 58% were women, and 47% were black. Mean body mass index was 30.8±7.1 kg/m 2, waist circumference was 102±17 cm, WHR was 0.91±0.08, and 80% had central obesity based on waist circumference and WHR criteria. After adjusting for multiple potential confounders (including age, sex, race, physical activity, body mass index, heart rate, smoking status, systolic blood pressure, fasting glucose, total cholesterol, antihypertensive medication use, glomerular filtration rate, left ventricular mass index, wall motion abnormalities, and ejection fraction), central obesity and WHR remained associated with worse global longitudinal strain, early diastolic strain rate, s′ velocity, and e′ velocity ( P <0.05 for all comparisons). There were no significant statistical interactions between WHR and obesity status. Conclusions—: In this cross-sectional study of participants with multiple comorbidities, central obesity was found to be associated with adverse cardiac mechanics. Abstract : Supplemental Digital Content is available in the text.